PENGARUH PEMBERIAN ZINK TERHADAP GAMBARAN HISTOPATOLOGI HATI MENCIT JANTAN (Mus musculus) YANG DIINDUKSI ANTIKANKER SIKLOFOSFAMID - M.Haqqul Syifa' Masyhur Hakim (2021)
This study was conducted to determine the effect of zinc on the histopathological picture of the liver of mice induced by cyclophosphamide. This study used 30 male mice which were divided into 6 groups. The negative control group was not given zinc and cyclophosphamide, positive control I was only given zinc, positive control II was only given cyclophosphamide, and 3 treatment groups were given cyclophosphamide 200 mg/Kg and zinc with a dose of zinc respectively 25 mg/Kg, 50 mg/Kg, and 100 mg/Kg. The treatment was carried out for 35 days followed by surgery, liver harvesting, preparation of preparations and Hematoxylin-Eosin staining. Liver damage was assessed using the Manja-Roenigk score. Positive control I had the lowest score while positive control II had the highest score. One Way ANOVA test results show a significance value (p= 0.000). The most effective zinc dose to improve the histopathological picture of the liver of mice is 100 mg/Kg. The results of this study showed that zinc had an effect on improving the histopathological picture of the liver of mice induced by cyclophosphamide.